Dynamic Social Integration: Social Integration of Religious Followers in Ambon - Saidin Ernas (Al-Albab, 2015)
The social dynamics in post-conflict Ambon, Maluku, 1999-2004, indicated that even though people were segregated in the Islamic-Christian areas, gradually social integration began to occur naturally. The process of integration that occurred also gave birth to new values and inclusive views that give hope to future peace building. Using the theory of social integration of dynamic adaptation of the Parsonian structural-functional classic paradigm and combined with a qualitative research model, this study successfully formulated several important findings. First, social integration occurred in the city of Ambon could run naturally through economic interactions, consensus on political balance and inclusive religious spirit. In addition, the presence of public spaces such as offices, schools, malls and coffee shops served as a natural integration medium that is increasingly important in the dynamics of the society. Second, the new social integration has created an increasingly important meaning that leads to a model of active harmony characterized by a process of the increasingly active social interaction between different religions, as well as strengthening pluralism and multiculturalism insight due to campaign by educational institutions and civil society groups. Third, this study also reminds us that although there has been a process of the increasingly positive social integration in Ambon city, people still need to be aware of the growth of radical religious ideologies at a certain level, and also of strengthening identity politics in the long run that will potentially give birth to primordial and ethnocentric attitudes that are harmful to the development of peace.